Indirect fabrication of versatile 3D microfluidic device by a rotating plate combined 3D printing system. Issue 66 (8th November 2018) - Ha, Dong-Heon; Ko, Dong-Hyeon; Kim, Jin-oh; Im, Do Jin; Kim, Byoung Soo; Park, Soo-Young; Park, Steve; Kim, Dong-Pyo; Cho, Dong-Woo
Abstract : Rapid on-demand sacrificial printing techniques using suitable combinations of resin and sacrificial materials would be desirable to fabricate versatile and functional microfluidic devices with complex designs and chemical resistance. Abstract : In the past decade, 3D-printing technology has been applied in the field of microfluidics to fabricate microfluidic devices for wide-ranging areas of study including chemistry, biology, medicine, and others. However, these methods face several limitations such as insufficient resolution and long fabrication time. In this study, versatile microfluidic devices with different functions were indirectly fabricated by a rapid sacrificial template printing process using a photocurable fluoropolymer with chemical durability. The Pluronic® F127 hydrogel as a sacrificial template was rapidly patterned on substrates by a non-lithographic printing process using a computer-controlled 3D-printing system. Viscous fluoropolymer was cast on the non-deformable template that was consequently removed by applying heat and negative pressure after UV curing. The chemical-resistant and transparent microchannels were oblate-hemispherical on the cross section. They were tested by performing a heterogeneous catalytic reaction as well as a photochemical reaction. The microchannels with controlled heights were devised to induce convection for functioning as a micromixer with asymmetric flows. Moreover, upon printing the Pluronic® F127 on both sides of the PFPE (perfluoropolyether–urethane dimethacrylate) membrane substrate, the 3D hybrid microfluidic device was embedded with a permeable membrane between the lower and upper channels, which is useful for gas–liquid chemical processes.